Adherence to national paediatric bronchiolitis management guidelines and impact on emergency department resource utilization. Issue 2 (21st February 2020) - Maki, Kate; Azizi, Hawmid; Hans, Prabhjas; Doan, Quynh
Abstract: Objective: To evaluate the association between the use of nonrecommended pharmacology (salbutamol and corticosteroids) per national bronchiolitis guidelines, either during the index visit or at discharge, and system utilization measures (frequency of return visits [RTED] and on paediatric emergency department [PED] length of stay [LOS]). Study Design: We conducted a retrospective case control study of 185 infants (≤12 months old) who presented to the PED between December 2014 and April 2017 and discharged home with a clinical diagnosis of bronchiolitis. Inclusion criteria included ≥ 1 viral prodromal symptom and ≥ 1 physical exam finding of respiratory distress. Cases were defined as infants who had ≥ 1 RTED within 7 days of their index visit and controls were matched for age and acuity but without RTED. Logistic regression analysis and multivariable linear regression were used to assess the odds of RTED and PED LOS associated with nonadherence to pharmaceutical recommendations per AAP and CPS bronchiolitis guidelines. Results: Use of nonrecommended pharmacology per national bronchiolitis guidelines was documented among 39% of the 185 study participants. Adjusting for acuity of index visit, age, severe tachypnea, oxygen desaturation, and dehydration, use of nonrecommended pharmacology was not associated with RTED (odds ratio [OR]: 0.98, 95% confidence interval [CI]: 0.47 to 2.03). Use of salbutamol and corticosteroids, however, were each independently associated with increased PED LOS (58.3 minutes [P=0.01] and 116.7 minutes [P<0.001], respectively). Conclusion: Nonadherence to the pharmaceutical recommendations of national bronchiolitis guidelines was not associated with RTED but salbutamol and corticosteroid use increased PED LOS.